2010
DOI: 10.1111/j.1473-2165.2010.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Original Contribution: Wound‐healing properties of nut oil from Pouteria lucuma

Abstract: Summary Background Cell migration, angiogenesis, inflammation, and extracellular matrix remodeling are key events in wound healing. Natural products, including fatty acids (FAs), can accelerate wound healing by modulating the aforementioned events. Aims This study aims to evaluate the effect of lucuma (Pouteria lucuma O Kezte) nut oil (LNO) on fibroblasts migration, angiogenesis, inflammation, bacterial and fungal growth, and wound healing. Methods GC–MS analysis of FAs methyl esters (FAMES) was used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 36 publications
0
21
0
5
Order By: Relevance
“…This process requires interactions between a variety of cell types, multiple cytokines, growth factors, and extracellular matrix (ECM) molecules [1]. Based on traditional medicine, studies have shown improvement in the healing process with the use of natural products [2], including vegetable [35] and animal oils [2, 68]. Fatty acids (FAs) from these oils can modulate events such as inflammation, cell migration, angiogenesis, and ECM remodeling [5], and they can also act as chemotactic agents for leukocytes and promote cell proliferation [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…This process requires interactions between a variety of cell types, multiple cytokines, growth factors, and extracellular matrix (ECM) molecules [1]. Based on traditional medicine, studies have shown improvement in the healing process with the use of natural products [2], including vegetable [35] and animal oils [2, 68]. Fatty acids (FAs) from these oils can modulate events such as inflammation, cell migration, angiogenesis, and ECM remodeling [5], and they can also act as chemotactic agents for leukocytes and promote cell proliferation [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…En el caso de la lúcuma, el plan de desarrollo deberá considerar a los productores, acopiadores, minoristas, mayoristas y la industria alimentaria como actores directos y las instituciones locales, junto a las limitaciones enunciadas por Díaz (2006) e incursionar en la competitividad orientada al comercio justo y aspectos ambientales (Eyzaguirre & Dennis, 2007;Ayuya et al, 2015) en mérito a sus propiedades nutracéuticas y cosméticas (National Research Council, 1989;Gonzales, 2007;Glorio et al, 2008;Rojo et al, 2010;Dini, 2011).…”
Section: Resultados Y Discusiónunclassified
“…Pav] O. Kze, de la familia de las Sapotaceae (Baehni y Bernardi, 1970), es una fruta nativa (León, 2000) que ha contribuido en la dieta básica de las familias pobres (National Research Council, 1989) y es alimento de varias especies de la fauna silvestre en la Amazonía (Gonzales, 2007). Por su incursión en la industria alimentaria (Gamboa et al, 2014), su sabor único altamente apreciado, sus propiedades nutracéuticas, cosméticas y medicinales (Glorio et al, 2008;Rojo et al, 2010;Dini, 2011), tiene un mercado interno y externo promisorio. La lúcuma se cultiva en huertos comerciales pero con mayor frecuencia en huertos familiares.…”
Section: Huertos Familiares En La Diversificación Del Ingreso Y En Launclassified
“…The gamma linolenic fatty acid (GLA) is a metabolite from the linoleic fatty acid and the first intermediate in the conversion of linoleic acid into arachidonic acid (Gustone, 1992). It is widely found in plants (Guil-Guerreiro, 2000;Knothe, 2013;Tso et al, 2013;Rojo et al, 2010). Some researchers have shown through the microbiologic analysis, that the gamma linolenic acid beyond its healing and nutritional characteristics, this fatty acid also shows antimicrobial characteristic (Desbois & Lawlor, 2013;Clement et al, 2008;Giamarellos-Bourboulis et al, 2004;Ramadan et al, 2008).…”
Section: Resultsmentioning
confidence: 99%